ANALISIS SENYAWA METABOLIT SEKUNDER DARI EKSTRAK METANOL DAUN SURIAN YANG BERPOTENSI SEBAGAI ANTIOKSIDAN - Yuhernita, Yuhernita; Juniarti, Juniarti (Makara Journal of Science, 2011)
Secondary Metabolites Analysis of Methanol Extract of Surian (Toona sureni (Bl.) Merr) Leaf as Antioxidant Potential. The study of performed secondary metabolites from the methanol extract of Surian (Toona sureni (Bl.) Merr) leaves have been done by thin-layer chromatography (TLC) method. The result showed that methanol extract of Surian leaves consist of alkaloid, flavonoid, polyphenol and terpenoid. All of them positively have the ability to scavenge 2,2- diphenyl-1-picrylhydrazyl (DPPH). It has IC50 (4.80) are smaller than the ascorbat acid standard (IC50 = 9.23).